Investigation of cerium (III) activated-ceria nanoparticles as corrosion inhibitors for carbon steel - Nguyen, A. S.; Nguyen, T. D.; Thai, T. T.; To, T. X. H. (Vietnam Journal of Science and Technology, 2018)
The present work investigated the corrosion protection performance of ions Ce3+ activated-cerium(IV) oxides nanoparticles for carbon steel in a NaCl solution. Ceria nanoparticles were synthesized by homogeneous precipitation in ethanol/water mixed solvent. The obtained CeO2 nanoparticles were characterized by X-ray diffraction (XRD) and transmission electron microscope (TEM). The corrosion inhibition action of the activated nanoparticles by cerium(III) ions on carbon steel in NaCl solution was evaluated by electrochemical measurements (electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization). Then, the effect of cerium salt activated-CeO2 on the protection properties of poly-vinyl-butyral (PVB) coating deposited onto carbon steel plate was studied by salt spray test. The obtained results showed that the salt activated-nanoparticles are anodic corrosion inhibitors. The presence of Ce3+ activated CeO2 in the coating improved the barrier properties and corrosion protection performance of the PVB coating. No swellings of coating were observed after 48 hours of exposure in salt spray chamber